Internalization of Islamic Da'wah Values through Sholawatan in the Kresendo Drumblek Art Performance in Kaliwungu, Kendal Regency - Mimbar, Muhammad Maftuh Ahnan Al; Wafa, Mochammad Usman (Lembaga Teewan Journal Solutions, 2026)
The Drumblek Kresendo art performance in Kaliwungu, Kendal Regency combines drumblek percussion rhythms with the chanting of sholawatan, creating a performance that serves as a medium for conveying Islamic da'wah values to the community. This study aims to examine the process of internalizing Islamic da'wah values through sholawatan within the Drumblek Kresendo performance art. The research employed a qualitative approach with a descriptive design. Data were collected through observation, interviews with group leaders, performers, and audience members, as well as documentation, and were analyzed through data reduction, data presentation, and conclusion drawing using source and technique triangulation. The findings indicate that sholawatan in drumblek performances functions as a form of cultural da'wah that internalizes religious values through the introduction of values via sholawat chanting, community participation in sholawatan activities, the appreciation of collective religious experiences, and the reinforcement of the religious identity of the Kaliwungu community through performance practices in various religious and cultural events.